Archiving Feminism: Papers, Politics, Posterity - Dever, Maryanne (Archivaria, 2014)
This article explores the process of securing for the National Library of Australia Merle Thornton’s personal archive, which documents decades of feminist activism. Thornton, a noted figure in Australia’s early second-wave women’s movement, is best known as one of the “Bar Room Suffragettes,” who in 1965 chained themselves to the front bar of the Regatta Hotel in Brisbane, demanding women’s right to drink alongside men in public bars. In reflecting on the process of securing these papers, the author poses a series of questions concerning archives and aging, the folding of personal history into collective memory, and the role of archival source material in determining the conditions of possibility for writing histories of feminist activism. Further, in reflecting on her own role in the project, the author asks whether it is possible to perform the work of “archiving feminism” on radically non-nostalgic terms that challenge the discursive positioning of second-wave activists as a generation whose political legacy is threatened by a contemporary “culture of forgetting.” Finally, the article necessarily engages with the tension between the archive as a memory device and the archive’s entanglement with anticipation and futurity. RÉSUMÉ Cet article explore le processus par lequel la bibliothèque nationale australienne a acquis les archives personnelles de Merle Thornton, qui documentent des décennies d’activisme féministe. Thornton, une personnalité éminente des débuts de la deuxième vague du mouvement féministe australien, est mieux connue comme l’une des « suffragettes des bars » (« Bar Room Suffragettes »), qui en 1965 se sont enchaînées au bar principal de l’hôtel Regatta à Brisbane, réclamant le droit des femmes de boire aux côtés des hommes dans les bars publics. En se penchant sur le processus par lequel on a sauvegardé ces documents, l’auteure pose une série de questions au sujet des archives et du vieillissement, de l’intégration de l’histoire personnelle dans la mémoire collective et du rôle des sources archivistiques pour fixer les conditions rendant possible l’écriture de l’histoire de l’activisme féministe. De plus, en se penchant sur son propre rôle dans ce projet, l’auteure se demande s’il est possible d’effectuer le travail de « l’archivage du féminisme » sur des bases radicalement nonnostalgiques qui contestent le positionnement discursif des activistes de la deuxième vague comme une génération dont le patrimoine politique est menacé par la « culture de l’oubli » contemporaine. Enfin, l’article aborde nécessairement la tension entre les archives comme mécanisme de la mémoire et l’enchevêtrement propre aux archives entre attentes et possibilités futures.